Recent Advances in Creep Modelling Using the θ Projection Method - William Harrison (Metals)
The theta projection method has been used to predict uniaxial creep curve shapes for a wide range of materials. However, one of the criticisms of the existing method is that the multilinear approach, commonly used to correlate theta parameters to applied test conditions, does not extrapolate well over a full range of creep conditions, due to not accounting for changes in creep mechanisms. This is particularly important for evaluating the creep behaviour of structural engineering components that operate in an environment in which a wide range of stress and/or temperatures exist during their service life. This study uses the theta projection method to evaluate creep curves for the nickel-based superalloy, Waspaloy, over a range of test conditions, considering changes in observed dominant creep mechanisms. A clear break in the trend of <semantics>θ3</semantics> and <semantics>θ4</semantics> with respect to stress is observed, indicating that a change in mechanism is important for tertiary creep. Using a power law approach along with optimisation algorithms, the residual error between predicted and experimentally observed creep curves is reduced. With more accurate prediction of creep curves, creep rates throughout the duration of creep can be more accurately calculated, providing the basis of more accurate computational creep models.